Genome-Wide Analysis of Heat-Sensitive Alternative Splicing in Physcomitrella patens. Issue 2 (28th April 2014) - Chang, Chiung-Yun; Lin, Wen-Dar; Tu, Shih-Long
Abstract : Alternative splicing is responsive to elevated temperature in nonvascular plants and can be rapidly modulated in specific genes for plants to cope with heat stress. Abstract: Plant growth and development are constantly influenced by temperature fluctuations. To respond to temperature changes, different levels of gene regulation are modulated in the cell. Alternative splicing (AS ) is a widespread mechanism increasing transcriptome complexity and proteome diversity. Although genome-wide studies have revealed complex AS patterns in plants, whether AS impacts the stress defense of plants is not known. We used heat shock (HS ) treatments at nondamaging temperature and messenger RNA sequencing to obtain HS transcriptomes in the moss Physcomitrella patens . Data analysis identified a significant number of novel AS events in the moss protonema. Nearly 50% of genes are alternatively spliced. Intron retention (IR ) is markedly repressed under elevated temperature but alternative donor/acceptor site and exon skipping are mainly induced, indicating differential regulation of AS in response to heat stress. Transcripts undergoing heat-sensitive IR are mostly involved in specific functions, which suggests that plants regulate AS with transcript specificity under elevated temperature. An exonic GAG-repeat motif in these IR regions may function as a regulatory cis-element in heat-mediated AS regulation. A conserved AS pattern for HS transcription factors in P. patens and Arabidopsis ( Arabidopsis thaliana ) reveals that heat regulation for AS evolved early during land colonization of green plants. Our results support that AS of specific genes, including key HS regulators, is fine-tuned under elevated temperature to modulate gene regulation and reorganize metabolic processes.